RELIGIOUS CONTACT AND LOANWORD STRATIFICATION IN INDONESIAN: A CORPUS-BASED STUDY - Jean Paul Gotopo (Universitas Islam Sumatera Utara (UISU), 2026)
This study examines how successive waves of religious contact—including Hindu-Buddhist, Islamic, and Christian influences—have contributed to loanword stratification in the Indonesian language. Religious contact has been a major driver of lexical borrowing across multilingual societies, yet its role in producing stratified loanword systems within national languages remains insufficiently understood. However, few studies have examined how successive waves of religious contact produce stratified lexical systems in contemporary Indonesian. Using a corpus-based analysis of 1,402 lexical items compiled from major dictionaries and national linguistic corpora, the study classifies loanwords according to their etymological origins and semantic domains. The results reveal a layered pattern of borrowing aligned with historical phases of religious and cultural contact. Sanskrit-derived terms constitute the largest group (31.2%), followed by Dutch (24.2%), Arabic (13.1%), and Portuguese (4.6%), with smaller contributions from Hindi, Pali, and regional languages. While these lexical strata reflect distinct historical influences, many borrowed forms have become fully integrated into contemporary Indonesian across religious, institutional, and everyday domains. The findings demonstrate that religious contact contributed not only to specialized religious vocabulary but also to broader layers of lexical borrowing that now form part of a shared sociolinguistic repertoire. By linking historical language contact with patterns of lexical integration, this study highlights how religious interaction can produce enduring stratification within the Indonesian lexicon.